2012
DOI: 10.1007/s00484-012-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated thermoregulatory responses with increased plasma osmolality in obese subjects during two seasons

Abstract: Obese subjects may be more vulnerable to injury from heat stress, and appear to be less efficient at thermoregulation. Sweat rate, tympanic temperature and osmolality in obese subjects were investigated in Japan during two seasons. The purpose of this study was to examine the relationship between obesity, thermoregulatory response and season. Five obese (BMI, 32.0 ± 4.9 kg/m²) and five non-obese (BMI, 23.2 ± 2.9 kg/m²) men participated in this experiment at latitude 35°10' N and longitude 136°57.9'E. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Second, as discussed above, the rate of temperature decline post mortem would be slower for the fatter, heavier carcasses resulting from grain feeding. Finally, obese humans are more susceptible to heat stress than nonobese individuals as they have a reduced ability to dissipate heat (Kanikowska et al 2013), and the same might be true of fat long-fed cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, as discussed above, the rate of temperature decline post mortem would be slower for the fatter, heavier carcasses resulting from grain feeding. Finally, obese humans are more susceptible to heat stress than nonobese individuals as they have a reduced ability to dissipate heat (Kanikowska et al 2013), and the same might be true of fat long-fed cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular and other fat accumulation is associated with insulin resistance in humans (Goodpaster et al 1997;Kim et al 2006;Komiya et al 2006) and obese individuals have difficulty dissipating heat (Kanikowska et al 2013). As reviewed by DiGiacomo et al (2014a), long grain feeding is known to increase fat deposition and is postulated to elevate circulating glucose and insulin, presumably through inducing a state of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found attenuated thermoregulatory responses among those with obesity (Kanikowska et al, ). One of the primary mechanisms driving this relationship is that adults with obesity may have an altered distribution of body fluid with a higher volume of extracellular relative to intracellular fluid (Stookey, Barclay, Arieff, & Popkin, ).…”
Section: Life Course Changes and Interactions With Health Conditions mentioning
confidence: 99%
“…The seasonal changes are executed through fluctuations in humoral signals, including leptin and ghrelin (Adam and Mercer 2004 ; Florant and Healy 2012 ). Interestingly, while leptin concentrations in humans do not exhibit consistent seasonal changes, it has been observed that the levels of leptin, cholesterol and triglycerides in obese males are significantly higher in winter (Kanikowska et al 2013 ).…”
Section: Rhythmicity Of Food Intake Gut Function and Metabolismmentioning
confidence: 99%